2007
DOI: 10.1038/sj.ki.5002055
|View full text |Cite
|
Sign up to set email alerts
|

Mitogen-activated protein kinase upregulation reduces renal D1 receptor affinity and G-protein coupling in obese rats

Abstract: Reactive oxygen species play a key role in pathophysiology of cardiovascular diseases by modulating G-protein-coupled receptor signaling. We have shown that treatment of animal models of diabetes and aging with tempol decreases oxidative stress and restores renal dopamine D1 receptor (D1R) function. In present study, we determined whether oxidation of D1R and upregulation of mitogen-activated protein kinases (MAPK) were responsible for decreased D1R signaling in obese animals. Male lean and obese Zucker rats w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

3
30
0
2

Year Published

2007
2007
2018
2018

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 23 publications
(35 citation statements)
references
References 36 publications
3
30
0
2
Order By: Relevance
“…8, 19). In agreement with our previous studies, we found that obese animals exhibit oxidative stress as evidenced by increased lipid peroxidation and advanced glycation end products along with decreased levels of glutathione and SOD activity, indicating a compromised antioxidant mechanism (6,7). Diabetes can induce oxidative stress via several mechanisms (8,19).…”
Section: Discussionsupporting
confidence: 80%
See 4 more Smart Citations
“…8, 19). In agreement with our previous studies, we found that obese animals exhibit oxidative stress as evidenced by increased lipid peroxidation and advanced glycation end products along with decreased levels of glutathione and SOD activity, indicating a compromised antioxidant mechanism (6,7). Diabetes can induce oxidative stress via several mechanisms (8,19).…”
Section: Discussionsupporting
confidence: 80%
“…Other circulating factors, such as free fatty acid and leptin, also contribute to increased reactive oxygen species generation (8,19). In agreement with these findings, our group has previously shown that obese Zucker rats are hyperinsulinemic, hyperlipidemic, and hyperglycemic, a hallmark of type 2 diabetes-associated obesity (6,7). Because the pathogenesis of diabetes as well as its complications involves oxidative stress, the use of antioxidant is an appealing concept (8,19).…”
Section: Discussionsupporting
confidence: 72%
See 3 more Smart Citations